1994
DOI: 10.1037/0022-3514.67.3.446
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of shared and unshared information in decision-making groups.

Abstract: The effects of task importance and group decision training on the discussion behavior of decisionmaking groups were investigated. Three-person groups decided which of 3 hypothetical faculty candidates would be the best person to teach an introductory psychology course. Prior to discussion, some of the information about each candidate was given to all group members (shared information), whereas the remainder was randomly divided among them (unshared information). In general, groups discussed much more of their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
218
2
11

Year Published

1996
1996
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(239 citation statements)
references
References 40 publications
(50 reference statements)
8
218
2
11
Order By: Relevance
“…Conversely, moderate time pressures allow groups to focus on the quality of output, so they more carefully attend to the available information. Consistent with this conclusion, Larson, Foster-Fishman, and Keys (1994) showed that groups mention unshared information relatively late in their discussions, implying that time restrictions increase the type of biases demonstrated by Titus ( 1985, 1987). Therefore, at least for complex tasks, restrictive time pressures might allow information-processing biases to play a larger role in group interaction and group decision making.…”
Section: Attentionsupporting
confidence: 72%
“…Conversely, moderate time pressures allow groups to focus on the quality of output, so they more carefully attend to the available information. Consistent with this conclusion, Larson, Foster-Fishman, and Keys (1994) showed that groups mention unshared information relatively late in their discussions, implying that time restrictions increase the type of biases demonstrated by Titus ( 1985, 1987). Therefore, at least for complex tasks, restrictive time pressures might allow information-processing biases to play a larger role in group interaction and group decision making.…”
Section: Attentionsupporting
confidence: 72%
“…Finally, another finding from social psychology shows that during group discussions, unshared information is mentioned relatively late, thus increasing the bias toward shared information when time pressure is high (Larson, Foster-Fishman, & Keys, 1994). Consequently, when buyers need to reach a decision quickly, the well-known brand is more likely to be in the center of the group discussion because of the group's shared information about it, which increases the likelihood of the brand's entering the consideration set.…”
Section: Time Pressurementioning
confidence: 99%
“…This research has reliably shown that teams rarely discover the hidden profile because they discuss proportionally more communal than unique information (Wittenbaum, Hollingshead, and Botero, 2004). Specifically, team members are more likely to mention, repeat (Larson, Foster-Fishman, and Keys, 1994), and rate communal information as more important, accurate, and relevant (Wittenbaum, Hubbell, and Zuckerman, 1999) than unique information.…”
Section: Performance In Teamsmentioning
confidence: 99%